2021
DOI: 10.1177/1045389x20978285
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel piezoelectric-actuated inertial pump using bionic valve

Abstract: Sampling fluids from the small-diameter deep pipeline is a challenging problem. In this paper, a very simple, piezoelectric-actuated inertial pump (PIP) is developed using a bionic valve to solve these problems. The PIP consists of simple components, including a cantilever beam piezoelectric actuator, a hard tube, and a bionic valve made of silicone. The fluid is driven by the inertial force generated in the vibration process of the tube. A new bionic valve inspired by a heart valve has been designed which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A piezo stack-based valve to resolve drawbacks of the hydraulic buck converter causing undesirable fluctuating forces was proposed where an active noise control technique using Filtered-X mean square algorithm was adopted to attenuate unwanted cancellate noises [22]. A simple inertial pump consisting of a cantilevered beam with the piezoelectric actuator and bionic valve made of silicone was proposed for the possible application to a heart valve with small flow resistance and large flow area [23]. The energy consumption of a four-way digital piezo stack-based valve was studied and demonstrated that a huge reduction of the electrical energy consumption during motion of switching and holding was achieved compared to other hydraulic on/off valves [24].…”
Section: Introductionmentioning
confidence: 99%
“…A piezo stack-based valve to resolve drawbacks of the hydraulic buck converter causing undesirable fluctuating forces was proposed where an active noise control technique using Filtered-X mean square algorithm was adopted to attenuate unwanted cancellate noises [22]. A simple inertial pump consisting of a cantilevered beam with the piezoelectric actuator and bionic valve made of silicone was proposed for the possible application to a heart valve with small flow resistance and large flow area [23]. The energy consumption of a four-way digital piezo stack-based valve was studied and demonstrated that a huge reduction of the electrical energy consumption during motion of switching and holding was achieved compared to other hydraulic on/off valves [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moradi-Dastjerdi et al [28] proposed a single chamber piezoelectric micropump with passive valves, and used a diaphragm made of passive polymeric membrane reinforced by nanoclay particles as the substrate bonded to the piezo-actuator to improve flow rate and back pressure of pump and the results showed that increasing the volume fraction of the nanoclay leads to the simultaneous increase in back pressure and flow rate of the pump. Ding et al [29] proposed a piezoelectric-actuated inertial pump, which was consisted of a cantilever beam piezoelectric actuator, a hard tube and a bionic valve made of silicon, and the results shows that the maximum flow rate of the pump was 170.25 mL min −1 under driving voltage with amplitude of 98 V and frequency of 24.5 Hz. He et al [30] proposed a single chamber piezoelectric micropump with passive valves with high output pressure and when the amplitude and frequency of the driving voltage was 220 V and 85 Hz respectively, its maximum output pressure was 27.41 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…When the frequency reaches a certain critical value, the piezoelectric pump has a dynamic balance, and the pump flow is reduced to zero, resulting in the phenomenon named known as “pump lagging of valve”. Valve-based piezoelectric pumps include: flexible-valve piezoelectric pumps [ 16 ], bionic-valve piezoelectric pumps [ 24 ], self-priming-valve piezoelectric pumps [ 25 ], etc. A special flow channel is employed in valve-less piezoelectric pumps to replace the valve structure in valve piezoelectric pumps, in which the pump-lagging of the valve is effectively avoided.…”
Section: Introductionmentioning
confidence: 99%